Butter Sculpture: The History of an Unconventional Medium. Issue 4 (December 2019) - Simpson, Pamela H.
With its roots in ancient food molds and table art for Renaissance banquets, butter sculpture in the United States debuted during the centennial and flourished in the first quarter of the twentieth century. As the dairy industry moved from farm to regional cooperative creameries and eventually to national brands, butter sculpture appeared at fairs and expositions. Both amateur and professional sculptors used this unusual medium for busts and portraits, dairy-related subjects, and models of buildings. The ephemeral nature of the medium and the novelty of food as art drew crowds to exhibits advertising butter as the natural, healthy alternative to oleomargarine.